2020
DOI: 10.1155/2020/2489890
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Generational Cohorts on the Preferences for Information and Communication Technologies in Latin American Patients with Obstructive Lung Diseases

Abstract: Background. Advances in information and communication technologies (ICTs) represent a growing platform for the expansion of healthcare related services, but there is little information on how generational differences might account for distinct patterns of use and interest for ICTs. Our study aims to achieve a better understanding on how generational cohorts might influence the use and preferences for ICTs among patients with obstructive lung diseases in Latin America. Materials and Methods. We conducted an ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73]. Moreover, cross-generational differences were studied in retailing regarding products in the non-food sector [74][75][76][77], in technology adoption or purchase [78,79], as well as politics [80].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73]. Moreover, cross-generational differences were studied in retailing regarding products in the non-food sector [74][75][76][77], in technology adoption or purchase [78,79], as well as politics [80].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar results have been reported where younger generations had the highest overall ICT usage compared to older cohorts. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 12 , 15 Previous studies found WhatsApp, e-mail, and SMS to be the most popular forms of electronic communication for receiving and seeking information as well as communicating with physicians among patients with chronic diseases . 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, different demographic factors, such as age/generation, gender, income, and educational level, still affect individuals' adoption and use of ICT, including social media. Among different demographic variables, generation has attracted some scholarly attention (e.g., Bailey & Ngwenyama, 2010;Cherrez-Ojeda et al, 2020;Metallo & Agrifoglio, 2015;Padayachee, 2018;Prensky, 2001;van Volkom et al, 2013) in different disciplines, such as communication, information, generational studies, and marketing. Based on the intergenerational communication perspective, technology use can either benefit or create barriers for intergenerational interactions (Bailey & Ngwenyama, 2010).…”
Section: Introductionmentioning
confidence: 99%